PENINGKATAN KUALITAS LULUSAN PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) NURUL HUDA KABUPATEN BEKASI MELALUI PENGELOLAAN EFEKTIF - Mulyanto, Agus; Fatah, Abdul; Khomaeni, Asep; Ichwan, Rusendra (Universitas Mataram, 2025)
Improving the quality of graduates is currently a major challenge and obstacle for PKBM. Factors that prevent PKBMs from meeting graduate competency standards include cost, time, and human resources. To deal with this problem, we need ingenuity and measures to more effectively and efficiently improve the quality of management and increase the number of graduates. Therefore, the service team organized a workshop to provide effective management support to PKBM Nurul Huda: 1) Improve human resources capacity to manage PKBM; 2) Increase the effectiveness of PKBM management; and 3) Adapt the PKBM curriculum to her DUDIKA's needs. This service is implemented through workshops to improve the quality of graduates and support for curriculum development tailored to DUDIKA's needs. The workshop activities conducted at PKBM Nurul Huda were successful in improving teachers' and administrators' understanding of the graduate competency standards and their needs at DUDIKA. Furthermore, the curriculum, especially for the Package C program, was developed through the development of educational modules using situated learning methods and project-based learning, adapted to all available resources.